ENHANCING LANGUAGE AWARENESS THROUGH BLOGGING: ENHANCING LANGUAGE AWARENESS THROUGH BLOGGING - S.Maratova, S.Maratova (Журнал иностранных языков и лингвистики, 2025)
Cognitive theories of language learning stress that active participation—where students examine and consider their language use—helps to build language awareness. Blogging applies these ideas by requiring critical participation via writing, peer comments, and edits. Based on sociocultural and metacognitive theory, blogging encourages language self-regulation, so enabling English language learners (ELLs) to internalize grammar, increase vocabulary, and raise communicative competency. Many of us believe that individual differences that are inherent in the learner can predict success or failure in learning.